9th International Scientific Conference “Business and Management 2016” 2016
DOI: 10.3846/bm.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Functional and personal income distribution in the Baltics: comparison of national and households accounts

Abstract: Abstract. In this paper we aim to cover the gap in analysis of functional distribution of National income at the macroeconomic level and personal income distribution at the microlevel. We compare the information provided in the National Accounts and in the EU Survey on Income and Living Conditions (EU-SILC) for the three Baltic states and in a wider EU context to establish the links between the economic prosperity at the macro level and income distribution at individual level. Comparative design helps identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Callan et al (2020) find that in Ireland only the top 1% of income is missing from household surveys as compared to register data, after accounting for concept differences. In line with this, Navicke and Lazutka (2016) show that capital income is underreported for Lithuania in EU-SILC, which is usually concentrated at the top of income distribution, while other income components are much less underreported. A study of Estonian Household Finance and Consumption Survey by Meriküll and Room (2019) showed that the rich as well as the poor usually do respond to surveys and so unit nonresponse is a smaller problem, but income is underreported due to item nonresponse.…”
Section: Data and Definitionssupporting
confidence: 70%
“…Callan et al (2020) find that in Ireland only the top 1% of income is missing from household surveys as compared to register data, after accounting for concept differences. In line with this, Navicke and Lazutka (2016) show that capital income is underreported for Lithuania in EU-SILC, which is usually concentrated at the top of income distribution, while other income components are much less underreported. A study of Estonian Household Finance and Consumption Survey by Meriküll and Room (2019) showed that the rich as well as the poor usually do respond to surveys and so unit nonresponse is a smaller problem, but income is underreported due to item nonresponse.…”
Section: Data and Definitionssupporting
confidence: 70%